THE INFLUENCE OF MANAGEMENT FUNCTIONS ON COMMUNITY SATISFACTION THROUGH SERVICE QUALITY FOR DISTRIBUTION OF 3 KG ELPIJI GAS SUBSIDIES FOR COMMUNITY MARKETS IN TANJUNG PINANG CITY - Rahma; Indrayani; Bambang Satriawan; Mohamad Gita Indrawan; Muammar Khaddafi (RADJA PUBLIKA, 2023)
This study aims to determine the influence of planning, organizing, actuating and controlling management functions on community satisfaction and service quality. The hypothesis proposed is that Planing affects community satisfaction, Organizing influences Community satisfaction, Actuating affects Community Satisfaction, Controlling affects Community satisfaction, Planning influences Service Quality, Organizing influences Service Quality, Actuating affects Service Quality, Controlling affects Service Quality Service Quality affects Community Satisfaction, Planning influences Community Satisfaction through Service Quality, Organizing Affects Community Satisfaction through Service Quality, Actuating influences Community Satisfaction through Service Quality, Controlling affects community satisfaction through service quality. The sample in this study was all Tanjungpinang city residents who held the Puan Molek card with a total of 199 respondents. The data obtained were analyzed using data analysis techniques with PLS software tools. The results of the study show that planning has a significant positive effect on service quality. Organizing has a significant positive effect on Service Quality. Actuacting has a significant positive effect on quality. controlling influenceService qualitysignificant positive. Planning has no significant positive effect on community satisfaction. Organizingaffect Community satisfaction significantly positive. Actuating has a significant positive effect on Community Satisfaction. Controlling Affects Community Satisfaction Positively Not Significantly, Planning for Community Satisfaction through Service quality is Positively Significant. Organizing community satisfaction through significant positive service quality. Actuating community satisfaction through significant positive service quality, controlling community satisfaction through significant positive service quality.